Using Household Surveys to Assess Missed Opportunities for Simultaneous Vaccination: Longitudinal Examples from Colombia and Nigeria - Dale A. Rhoda; Mary L. Prier; Caitlin B. Clary; Mary Kay Trimner; Martha Velandia-Gonzalez; M. Carolina Danovaro-Holliday; Felicity T. Cutts (Vaccines, 2021)
One important strategy to increase vaccination coverage is to minimize missed opportunities for vaccination. Missed opportunities for simultaneous vaccination (MOSV) occur when a child receives one or more vaccines but not all those for which they are eligible at a given visit. Household surveys that record children’s vaccination dates can be used to quantify occurrence of MOSVs and their impact on achievable vaccination coverage. We recently automated some MOSV analyses in the World Health Organization’s freely available software: Vaccination Coverage Quality Indicators (VCQI) making it straightforward to study MOSVs for any Demographic & Health Survey (DHS), Multi-Indicator Cluster Survey (MICS), or Expanded Programme on Immunization (EPI) survey. This paper uses VCQI to analyze MOSVs for basic vaccine doses among children aged 12–23 months in four rounds of DHS in Colombia (1995, 2000, 2005, and 2010) and five rounds of DHS in Nigeria (1999, 2003, 2008, 2013, and 2018). Outcomes include percent of vaccination visits MOSVs occurred, percent of children who experienced MOSVs, percent of MOSVs that remained uncorrected (that is, the missed vaccine had still not been received at the time of the survey), and the distribution of time-to-correction for children who received the MOSV dose at a later visit.